Serial changes in high-sensitivity troponin I levels indicate poorer prognosis in patients with suspected acute coronary syndrome who fail to reach a level greater than the 99th percentile. (25th November 2020) - Pareek, M; Kragholm, K.H; Byrne, C; Pallisgaard, J.L; Lee, C.J; Bonde, A.N; Fosboel, E.L; Gislason, G.H; Koeber, L.V; Bhatt, D.L; Torp-Pedersen, C
Abstract: Background: According to the fourth universal definition of myocardial infarction (MI) consensus paper, patients with changing troponins who do not reach a concentration greater than the 99th percentile may still be at high risk and should be followed closely. Purpose: To determine long-term prognostic implications of high-sensitivity troponin I (hs-TnI) levels and their relative change (Δ) from baseline in subjects with suspected acute coronary syndrome (ACS). Methods: We conducted a retrospective cohort study through individual participant-level linkage between Danish national registries. Subjects with a final discharge diagnosis of acute MI, unstable angina, suspected MI, or chest pain from October 2013 through December 2016 who had a record of at least two serial hs-TnI (Dimension Vista®, Siemens Healthineers, Erlangen, Germany; 99th percentile: 45 ng/l) measurements during hospitalization comprised the study population. Kaplan-Meier analysis and multivariable Cox regression, incorporating the competing risk of death, were used to examine the prognostic implications of serial hs-TnI. Subjects were categorized according to whether their first and second hs-TnI were normal/elevated as well as Δhs-TnI and its direction, the latter using cut-offs for Δhs-TnI rises and/or falls of 20% and 50%, extrapolated from the recommendations for troponin T. The primary outcome was a composite of death from cardiovascular causes, recurrent MI, or repeat revascularization (i.e. not including the index event unless the patient died) at 12 months. Results: A total of 14, 514 individuals (mean age 62.2 years, 46.6% women) were included of whom 3407 (23.5%) had a final diagnosis of MI, 667 (4.6%) of unstable angina, and 10, 440 (71.9%) of either suspected MI or chest pain. Median baseline hs-TnI was 15 ng/l (25.3% elevated), second hs-TnI 15 ng/l (29.4% elevated), Δhs-TnI 0%, and time between samples 6.2 hours. At 12 months, 909 (6.3%) first primary events had occurred. Baseline hs-TnI and Δhs-TnI both displayed a significant, non-linear association with the primary outcome (P<0.001). The Figure shows the prognostic implications of serial hs-TnI. Overall, subjects with two consecutively elevated hs-TnI had the highest 12-month event risk (15.7%), followed by those who went from a normal to an elevated hs-TnI (9.9%), those who went from an elevated to a normal hs-TnI (4.2%), and those with two normal hs-TnI (2.7%). Most either had no significant Δhs-TnI (−20% to 20%: 74.9%) or a large positive Δhs-TnI (>50%: 17.5%). Individuals with any Δhs-TnI (>20% in either direction) had a worse prognosis than those without. This was also true for the group of individuals with two normal hs-TnI (event risk 7.8% in those with a Δhs-TnI >20% versus 2.3% in those without, P<0.001). Conclusions: Δhs-TnI was an important determinant of poorer prognosis in subjects with suspected ACS, even among individuals who did not reach a concentration greater than the 99th percentile. Funding Acknowledgement: Type of funding source: None